Bioethics: why philosophy is essential for progress. Issue 1 (16th December 2014) - Savulescu, Julian
Abstract : It is the JME 's 40th anniversary and my 20th anniversary working in the field. I reflect on the nature of bioethics and medical ethics. I argue that both bioethics and medical ethics together have, in many ways, failed as fields. My diagnosis is that better philosophy is needed. I give some examples of the importance of philosophy to bioethics. I focus mostly on the failure of ethics in research and organ transplantation, although I also consider genetic selection, enhancement, cloning, futility, disability and other topics. I do not consider any topic comprehensively or systematically or address the many reasonable objections to my arguments. Rather, I seek to illustrate why philosophical analysis and argument remain as important as ever to progress in bioethics and medical ethics.